Підходи до формування синергетичного ефекту в економіці - Шматько, Наталія Михайлівна (Українська державна академія залізничного транспорту, 2013)
У статті розглянуто теоретичні основи поняття синергетичного ефекту, розглянуто сутність синергетичного ефекту та синергетичної економіки, як економічної категорії сучасного відтворення і її забезпечення фінансово-економічними відносинами, розглянуто способи вимірювання синергетичного ефекту та запропоновано функціональний синергізм між різними групами галузей, визначено, що виявлено, що гроші та їх рух (потоки) виступають в якості одного з факторів реального відтворення і у складі комплексу різнорідних чинників, які здатні надавати безпосередній вплив на утворення синергетичного ефекту.

The article deals with the theoretical foundations of the synergy concept, the essence synergy and synergy economy, as an economic category and its modern reproduction of the financial and economic relations. Also, it deals with how to measure the synergistic effect of joint conduct of operations: either evaluation of the reduction of costs for a given level of income either assessment increase profits for a given level of investment. So, when entering into a new strategic area of economic production initial losses and later operational losses will be different. This indicates the presence of two types of synergy: the initial and operational. It was proposed functional synergism between different groups of industries, determined that synergies can be created only in a real economy, since this type of effect is the result of a combination of factors. This combination of factors contain production, consumption, exchange and distribution of primary resources and created wealth. It was defined that money and their movements (flows) stands as the factor of real reproduction. They as a part of complex of different factors can make direct influence on the formation of synergies.
Approaches to formation synergistic effect in the economy
Keywords: синергетичний ефект; синергізм; синергетична економіка; ефект синергізму; synergic effect; synergy; synergic economy; effect of synergism